Caesarean Section and Perinatal Mortality in South Western Nigeria - Ezechi, OC; Loto, OM; Ndububa, VI; Okogbo, FO; Ezeobi, PM; Nwokoro, CA (Nepal Journal of Obstetrics and Gynaecology, 2010)
Aim: Caesarean section carries a substantial hazard to the unborn fetus, especially if done as an emergency procedure. In our environment fetal loss following a caesarean delivery is usually attributed to the procedure by patients and relations who do not readily accept caesarean section as a delivery option. Method: A 10 year descriptive study of caesarean section related perinatal mortality in four tertiary hospitals in South western Nigeria. Results: Nineteen thousand one hundred and seventy nine deliveries were conducted in the hospitals during the study period; five thousand one hundred and ninety five (27.1 %) of which were caesarean deliveries. Two hundred and thirty five of the caesarean deliveries were associated with perinatal death (6.9 %.). Majority of these deaths were among the unbooked (73.8%), multiparous (69.0 %) patients and emergency caesarean delivery (83.4%). Prolonged/ obstructed labour (45.4%), preeclampsia/eclampsia (18.8%) and fetal distress (11.5%), were the commonest indication for caesarean deliveries. While majority of the perinatal death were still born (60.3%), (39.7%) were early neonatal deaths. The common causes of early neonatal death in these patients were severe birth asphyxia (37.4 %), neonatal sepsis (22.0%) and prematurity (16.4%). Conclusion: The cause of perinatal mortality associated with caesarean delivery in our environment are preventable with public enlightenment, provision of affordable and accessible prenatal and neonatal care, discipline, behavioural and attitudinal change of health workers, and the political will on the part of policy makers to maternal and child health delivery care more effective. DOI: 10.3126/njog.v4i1.3332 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 46-48